2017
DOI: 10.1016/j.neuroscience.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexcitability in synaptic and firing activities of spinal motoneurons in an adult mouse model of amyotrophic lateral sclerosis

Abstract: Hyperexcitability is hypothesized to contribute to the degeneration of spinal motoneurons (MNs) in amyotrophic lateral sclerosis (ALS). Studies, thus far, have not linked hyperexcitability to the intrinsic properties of MNs in the adult ALS mouse model with the G93A-mutated SOD1 protein (mSOD1G93A). In this study, we obtained two types of measurements: ventral root recordings to assess motor output and intracellular recordings to assess synaptic properties of individual MNs. All studies were carried out in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…; Jiang et al. ). The enhancement of mitochondrial fusion and/or the inhibition of mitochondrial fragmentation ameliorates neuronal degeneration in ALS models (Song et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Jiang et al. ). The enhancement of mitochondrial fusion and/or the inhibition of mitochondrial fragmentation ameliorates neuronal degeneration in ALS models (Song et al.…”
Section: Discussionmentioning
confidence: 98%
“…induced pluripotent stem cell (IPSC)-derived MN from patient fibroblasts (Sareen et al, 2013;Wainger et al, 2014;Devlin et al, 2015;Naujock et al, 2016), cultured MN derived from spinal cord of early postnatal or embryonic mice (Pieri, 2003;Kuo et al, 2004;Kuo et al, 2005;Martin et al, 2013) or acutely isolated spinal cord/brain stem slices (Kuo et al, 2004;Bories et al, 2007;van Zundert et al, 2008;Pambo-Pambo et al, 2009;Quinlan et al, 2011;Martin et al, 2013;Leroy et al, 2014;Jiang et al, 2017; Figure 3 and Tables 3, 4). Thanks to recent advances in stem cell research, it is now possible to study the excitability and activity of MN derived from human patients' fibroblasts through the generation of IPSC.…”
Section: Excitability Changes Of Lmnmentioning
confidence: 99%
“…Furthermore, a substantial fraction of those had lost their ability to fire repetitively, arguing for the hypoexcitability of LMN in early stages in vivo (Delestrée et al, 2014). Seemingly at odds with these findings, are data pointing toward increased excitability of LMN (prolonged repetitive firing and higher frequency of spontaneous EPSPs) upon the stimulation of the dorsal root in acutely isolated sacral spinal cords obtained from presymptomatic − early symptomatic (P50−P90) SOD1 G93A tg mice (Jiang et al, 2017). Interestingly, based on pharmacological testing Jiang et al propose that the observed changes in spontaneous depolarization originate at least in part from spinal network inputs rather than through the peripheral afferents (Jiang et al, 2017).…”
Section: Excitability Changes Of Lmnmentioning
confidence: 99%
See 2 more Smart Citations